Label‐free quantitative analysis of the membrane proteome of Bace1 protease knock‐out zebrafish brains. Issue 9 (2nd April 2013) - Hogl, Sebastian; van, Frauke; Dislich, Bastian; Kuhn, Peer‐Hendrik; Haass, Christian; Schmid, Bettina; Lichtenthaler, Stefan F.
<x xml:space="preserve">Abstract</x> The aspartyl protease BACE1 cleaves neuregulin 1 and is involved in myelination and is a candidate drug target for Alzheimer's disease, where it acts as the β‐secretase cleaving the amyloid precursor protein. However, little is known about other substrates in vivo. Here, we provide a proteomic workflow for BACE1 substrate identification from whole brains, combining filter‐aided sample preparation, strong‐anion exchange fractionation, and label‐free quantification. We used bace1‐deficient zebrafish and quantified differences in protein levels between wild‐type and bace1 −/− zebrafish brains. Over 4500 proteins were identified with at least two unique peptides and quantified in both wild‐type and bace1 −/− zebrafish brains. The majority of zebrafish membrane proteins did not show altered protein levels, indicating that Bace1 has a restricted substrate specificity. Twenty‐four membrane proteins accumulated in the bace1 −/− brains and thus represent candidate Bace1 substrates. They include several known BACE1 substrates, such as the zebrafish homologs of amyloid precursor protein and the cell adhesion protein L1, which validate the proteomic workflow. Additionally, several candidate substrates with a function in neurite outgrowth and axon guidance, such as plexin A3 and glypican‐1 were identified, pointing to a function of Bace1 in neurodevelopment. Taken together, our study provides the first proteomic analysis of knock‐out zebrafish tissue and demonstrates that combining gene knock‐out models in zebrafish with quantitative proteomics is a powerful approach to address biomedical questions.